iPhone 3.0 road map to obsolescence. - Ochs, Susie
iPhone 3.0 will boast more than 100 new features--but what about the third-party apps that bring you those features right now?
Keywords: iPhone (Smartphone); Video recording; Landscapre keyboard; MMS Rescue